Continuing a time-honored praxis through characterization of traditional smoked meat delicacy (kinuday) - Garambas, Cynthia Depolio; Chua, Consuelo T., PhD.; Luna, Myrna Benita Z., PhD. (Quezon City University of the Philippines Diliman, 2021)
Every culture protects their indigenous knowledge and practices, for these distinguish them from other cultures. However, time-honored praxis becomes history when not transmitted and sustained. The inquiry described the traditional processing methods in preparing smoked meat dubbed as kinuday, produced by one of the ethnolinguistic tribes in the Cordillera – the Ibaloy Indigenous Ethnic group; characterized kinuday in terms of color, aroma, visual dryness, texture, saltiness, and smoky flavor; and evaluated the authenticity and accuracy of the generated documentary. Qualitative specifically, an ethnographic research design was utilized to describe the traditional practice in kinuday making. A quantitative experimental research design was employed in determining the organoleptic and physicochemical characteristics of kinuday. A descriptive research design was used to evaluate the authenticity and accuracy of the generated documentary. Unique processing methods employed by the Ibaloy IP group in meat smoking include use of swine specifically native breed in kinuday making; utilization of non-resinous type of wood as smoking material; use of a unique tool (owik) and silver grass as mat during the slaughtering process; practice hot/ warm smoking technique in kinuday processing; one day continuous to one month intermittent smoking duration; and hanging the kinuday on top of the cooking area (so-olan) until fully consumed. For kinuday organoleptic characteristics, results established that smoking duration affects the sensory qualities of kinuday, specifically its uncooked outer skin and lean color, cooked inner lean color, saltiness, and smoky flavor. The other attributes were not affected by smoking duration. Regarding physicochemical characteristics, 36-hour smoked kinuday yields a higher pH level and sodium content than 24-hour smoked kinuday; however, water activity remains the same regardless of the length of smoking. Color differences for skin, fat and lean considering smoking duration as a factor are very distinct, distinct, and with a slight difference, respectively. Finally, the details indicated in the generated documentary were deemed authentic and accurate.
Dissertation
Bibliographical references (pages 154- 167)
Keywords: Smoked meat -- Philippines -- Benguet; Food -- Preservation -- Philippines; Smoking of food -- Philippines -- Benguet; Meat -- Preservation -- Benguet -- Philippines